Critical Review of Healthcare Policy Innovations: Transforming Global Health Delivery Systems - Al-Sogour, Ali Gourab Marrzoq; Alsiary, Mariam Mohammed; Maashi, Heala Ahmed Mohammed; Bakhashwain, Afnan Omar; Nahhas, Amani Faisal; aljohani, Ghadeer Abdullah; Al saiari, Huda Mohammed; Alabbas, Reyoof Jabr; Rafadah, Mohamed Hammad; AlSubaei, Jawhara Mobarak (Journal of Ecohumanism, 2024)
This paper reviews recent contributions to the development of healthcare policies and analyzes their implications for the ongoing and future changes in healthcare delivery systems worldwide. It looks at how policy innovations that seek to solve persistent issues and problems relating to healthcare, such as access, quality, and costs, are achieved. There is a particular emphasis on the coming collaborative ideas like UHC, accounts receivable systems, MACRA, MAC-P, and RECOVERY models, as well as digital health technology. These innovations are analyzed for their effectiveness in enhancing the health of patients, the general cost of the provision of healthcare, and the total satisfaction of the patient. Through comparisons of national and international policy changes, the paper shows the strengths and weaknesses of these reforms. It also points to some of the areas that need better improvement in healthcare systems all over the world. The main topics, such as health inequalities, the involvement of private-public partnerships, and technology, are presented so that the reader gets a clear picture of all the existing problems. Thus, the study indicates there have been strides made towards attaining the objectives of increasing coverage of health facilities and the quality of delivered health care; however, continued effort is required to remove barriers restricted by race and ethnicity to guarantee equal coverage for every society. In the same tone, the paper outlines recommendations that may be put to use and implemented in future reforms of healthcare policies in order to enhance healthcare delivery systems, operational efficiency, and stability in the global market.